Analisis Optimasi Transaksi Digital pada Sistem Informasi Pengadaan Sekolah (SIPLAH) PT. Intan Pariwara - Hasian Syuhada Syahraputra Siregar; Nur Wening (FEB Universitas Maritim Semarang, 2022)
This study aims to determine the optimization of digital transactions in the School Procurement Information System (SIPLah) at PT. Intan Pariwara. The research analysis used was an analysis with a qualitative descriptive approach. While the data collection method uses interview methods and observation methods. The results of the research on each parameter, the technology, marketing, transaction, customer service, product management and finance. SIPLah PT. Intan Pariwara has advantages compared to other SIPlah partners in the system and website appearance. Even so, it still has disadvantages, namely for the payment method it only has one payment method which makes the buyer have no choice.